2011
DOI: 10.1021/nn103130q
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Monodispersed Mesoporous Silica Nanoparticles with Ultralarge Pores and Their Application in Gene Delivery

Abstract: Among various nanoparticles, the silica nanoparticle (SiNP) is an attractive candidate as a gene delivery carrier due to advantages such as availability in porous forms for encapsulation of drugs and genes, large surface area to load biomacromolecules, biocompatibility, storage stability, and easy preparation in large quantity with low cost. Here, we report on a facile synthesis of monodispersed mesoporous silica nanoparticles (MMSN) possessing very large pores (>15 nm) and application of the nanoparticles to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
233
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 340 publications
(246 citation statements)
references
References 34 publications
8
233
1
Order By: Relevance
“…1 and Supplementary Note 1) were developed as a proteasome transporter. MSNPN were synthesized to have pore sizes between 25 and 30 nm using a pore expansion strategy 12,13 , which can harbour a proteasome holoenzyme molecule through noncovalent interactions with the polyhistidine (His) tag of proteasomes (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplementary Note 1) were developed as a proteasome transporter. MSNPN were synthesized to have pore sizes between 25 and 30 nm using a pore expansion strategy 12,13 , which can harbour a proteasome holoenzyme molecule through noncovalent interactions with the polyhistidine (His) tag of proteasomes (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…15,18 Second, nanosize particles lead to higher cellular uptake compared to the micrometer size particles. 4,16 From these results, we see the potency of using large pore mesoporous silica nanoparticles (LP-MSNs) as carriers for siRNA delivery. However, the successful application of LP-MSNs for delivery of nucleic acidbased drugs requires surface modification of the silica in order to generate sufficient binding affinity for the negatively charged nucleic acids.…”
mentioning
confidence: 95%
“…Following this premise, the group of Min compared the loading and release behaviour of both MSNs (2.1 nm) and LP-MSNs (23 nm) functionalized with amino groups. 107,108 They suggested that large-pore particles were able to host nucleic acids into their structure while regular-pore MSNs could only adsorb them at the surface. To demonstrate this, the authors loaded the corresponding nanoparticles with either the GFP plasmid DNA 107 or its opposite the GFP siRNA 108 and submitted both materials to a nuclease enzymatic prior to an in vitro testing.…”
Section: Loading Nucleotides Into Msns: New Devices For Transfection mentioning
confidence: 99%